Malnutrición y su relación con aspectos de salud en adultos mayores (2019)
ABSTRACT: Older adults have risk of malnutrition be- cause of changes in the ageing in physical, psychological and social aspects, also by modification in lifestyle. Objective: To explore the relationship between malnutrition with aspects of health and lifestyle in a group of non-institutionalized elderly. Materials and methods: A cross-sectional study was conducted in 178 adults ≥ 60 years who attended dental appointments at University outpatient center of the city of Medellin. We included those who were able to answer the questionnaires and without physical limitations that would prevent the taking of anthropometric measurements. As dependent variable malnutrition, as assessed by the Mini Nutritional Assessment; as independent variables demographic aspects, indicators of objective and subjective oral health, health perception and depressive risk were considered. A logistic regression was used to establish the association of risk of malnutrition/malnutrition with independent variables. Results: The percentage of people at risk of malnutrition/malnutrition was 31.5% according to Mini Nutritional Assessment. This percentage was significantly higher in adults who did not practice physical activity, with depressive Symptoms, presence of dental caries and a low score of Geriatric Oral Health Assessment Index (p<0.05). The crude logistic regression model and after adjusted for sex, age, alcohol consumption, smoking, physical activity, showed that the risk of malnutrition was associated with depressive symp- toms (OR=6.6 95% CI: 2.1-20.9), low level of General Oral Health Assessment Index (OR=4.1 95% CI: 1.3-12.7), presence of dental caries (OR=3.1 95% CI 1.2-8.1) and drug number consumed (OR=1.23 95% CI: 1.0-1.5). Conclusion: The probability of risk of malnutrition/malnu- trition was higher in older adults with impaired oral health, depressive symptoms and drug use.